Facebook e a plataformização do jornalismo : uma cartografia das disputas, parcerias e controvérsias entre 2014 e 2019 - Amanda Chevtchouk Jurno (2020)
In this PhD dissertation we aim to analyze the process of "platformization" of journalism by Facebook, focusing on the disputes and controversies surrounding the commercial, technological and editorial partnerships established between the platform and journalistic institutions. Platformization refers to the process of intermingling and mutual molding between the logic of online platforms and different social sectors. In the case of journalism, Facebook offers itself as an infrastructure that promises solutions and demands adjustments in the institutions' practices and operating logic. Our study is concentrated between the months of January 2014 and July 2019. In this period, we identified two main moments of this platforming process: the first is centered on the implementation of the Instant Articles tool, through which, since 2015, the platform seeks to establish itself as an infrastructure for the production, circulation and monetization of journalistic content; the second is organized around the Facebook Journalism Project, an initiative launched in 2017 in order to strengthen ties and stir the journalistic sector through initiatives such as project financing, training, and partnerships with fact-checking agencies. The research is also dedicated to analyze two moments of crisis: the mediation of content in the Trending Topics and the deletion of the photograph The Terror of War. Taken as “algorithmic controversies”, these situations that occurred in 2016 allow us to understand how a growing questioning of supposed neutrality of the Facebook agencies was decisive in the adjustments that were proposed for the platformization of journalism. Our theoretical framework is composed of concepts linked to Science and Technology Studies, more specifically to Platform Studies, Critical Algorithm Studies and Actor-Network Theory. The controversy cartography and “the connective approach” model (VAN DIJCK, 2013a) are our main methodological inspirations. Among the authors with whom we work are Van Dijck et al. (2018), Helmond (2015), Helmond et al. (2018), Bucher (2012 and 2018), Bucher and Helmond (2017), Plantin et. al (2018), Nieborg and Poell (2018), Gillespie (2010, 2018), Napoli and Caplan (2018).